DIGITAL TRANSFORMATION AND DISTRIBUTION EFFICIENCY IN SMALL AND MEDIUM ENTERPRISES (SMES) - Gondekar, Subhaan; Satsangi, Priya; Sharma, Bhawna (International Journal of Engineering Technologies and Management Research, 2025)
This research paper examines how digital transformation has reshaped distribution efficiency among small and medium enterprises (SMEs) in India. With increasing competition and evolving market dynamics, SMEs are adopting digital tools such as ERP systems, cloud computing, and digital logistics platforms to enhance transparency, speed, and cost-effectiveness. The paper explores the relationship between digital adoption and improvements in order accuracy, communication, inventory management, and customer satisfaction. Through an analytical review of academic literature, government reports, and industry studies, the paper highlights how digitalization can minimize delays, reduce costs, and optimize supply chain coordination. It also identifies common barriers faced by SMEs, including limited resources, skill gaps, and technological constraints. The study concludes with recommendations for policymakers and managers to promote digital readiness and sustainable growth within the SME sector.